Pengaruh Model Pembelajaran Connected Mathematic Project terhadap Kemampuan Pemecahan Masalah Matematika - Witri Lestari (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The purpose of the research is to determine the Impacts of Connected Mathematics project Learning Method on  Student’s Mathematics Problem solving Skills at SMP Putra Bangsa. The research method is experiment. Sample of the research is taken from affordable population by using cluster random sampling technique. Size of population is 40 students that divided into two class. The instrument used is essay test as much as 6 items. Analysis technique in this research is  t test. Testing requirements of data analysis is Liliefors test for normality and fisher test for homogeneity test. In experiment class   L test = 0.1143 and L table = 0.190. in control class L test = 0.0868 and L table=0.190, because L test ? L table, so Ho is received and it can be concluded that the data of the population in normal distribution. F test for homogeneity , F test=1.826 and F table=2.17, because F test? F table, so both of class has same varians or homogen. The result of data analyze t test=3.16 and t table=2.03 at significance level ?=0.05 and freedom degrees=38, so there are impacts of connected mathematics project learning model on mathematics problem solving skills.